From Literacy to Reality: Generation Z’s Perception of Early Marriage Practices in Urban Muslim Society - Pramesti, Erisa Nur’Adhani; Pabbajah, Mustaqim; Deraman, Deraman (Institut Agama Islam Negeri Kendari, 2025)
The low interest in literacy among Generation Z has led to limited knowledge and understanding regarding early marriage. This condition contributes to the increasing prevalence of early marriage practices, which remain difficult to control, particularly within urban Muslim societies. This study aims to explore Generation Z’s perception and literacy level concerning early marriage practices, as well as to examine the gap between literacy (knowledge) and social reality (practice). This study used a descriptive qualitative method. It had three steps. First, the researcher prepared the research tools and plans. Second, data were collected through interviews and documents about Generation Z’s views on early marriage in an urban Muslim society. Third, the data were analyzed by organizing, coding, and interpreting the information to identify themes related to how Generation Z views early marriage. The findings reveal that Generation Z’s literacy on early marriage remains relatively low. The main factors include a lack of personal awareness, insufficient parental guidance, and limited socialization from the government and religious institutions. This lack of literacy contributes to the rise of early marriage cases, which often result in divorce due to emotional and economic immaturity. The study highlights the importance of promoting critical literacy and contextual education among Generation Z to enhance their awareness of the risks of early marriage and to encourage them to make more mature, well-informed marital decisions.